Human Development Through Economic Empowerment Using Microfinance as a Fulcrum - Nampalli, Sreenivas; Subramanya Sarma, V. V. (Indian Journal of Finance, 2013)
Microfinance is the provision of financial services to low income clients, solidarity lending groups, and self employed, who traditionally lacked access to banking and related services. The human development framework sees 'income' as the "means" of development rather than as the "end" and includes all aspects of life, including political, economic, and cultural development. Income is the major determinant of economic empowerment. Women's economic empowerment is a multidimensional aspect and ,therefore, one factor does not satisfactorily provide its measurement. The other factors that are operationalized to measure economic empowerment of women are savings, accessibility to credit, and asset possession. Microfinance plays a significant role in improving the status of self help group families and their children in terms of improving their standards of living. The present study assesses the role of microfinance on the living conditions of the individual households in the pre-SHG and post-SHG scenario. The study suggests that microfinance significantly improved the poor respondents' access to financial services, and had a considerable positive impact on the human development of SHG members in the post-SHG period as compared to the pre-SHG period.